Working in the third space: promoting interdisciplinary collaboration to embed English language development into the disciplines - Briguglio, Carmela (Department of Industry, Innovation, Climate Change, Science, Research and Tertiary Education, 2014)
This project aimed to build on best practice research in the field, which indicates that embedding English language development into discipline content (that is, in teaching and learning) is most likely to have the greatest success in developing students’ English language proficiency. In particular, this fellowship addressed two priority areas that were identified in OLT projects for 2012:• Strategic approaches to learning and teaching which enhance student access and progression, and respond to student diversity; and• Disciplinary and cross-disciplinary leadership to enhance learning and teaching through leadership capacity building in discipline structures, communities of practice and cross-disciplinary networks.